The role of DPYD and the effects of DPYD suppressor luteolin combined with 5‐FU in pancreatic cancer - Hiroyuki Kato; Motonori Sato; Aya Naiki‐Ito; Shingo Inaguma; Makoto Sano; Masayuki Komura; Yuko Nagayasu; Kuang Xiaochen; Akihisa Kato; Yoichi Matsuo; Hideaki Ijichi; Satoru Takahashi (Cancer Medicine)
Abstract Background Despite advances in the treatment of cancer, pancreatic ductal adenocarcinoma (PDAC) remains highly lethal due to the lack of effective therapies. Our previous study showed that Luteolin (Lut), a flavonoid, suppressed pancreatocarcinogenesis and reduced the expression of dihydropyrimidine dehydrogenase (DPYD), an enzyme that degrades pyrimidines such as 5‐fluorouracil (5‐FU), in PDACs. In this study, we investigated the role of DPYD and evaluated the therapeutic potential of combining 5‐FU with Lut in PDACs. Methods and Results PDAC cells overexpressing DPYD showed increased proliferation, and invasiveness, adding to the resistance to 5‐FU. The xenograft tumors of DPYD‐overexpressing PDAC cells also exhibit enhanced growth and invasion compared to the control xenograft tumors. RNA‐seq analysis of the DPYD‐overexpressing PDAC xenograft tumors revealed an upregulation of genes associated with metallopeptidase activity—MMP9 and MEP1A. Furthermore, the overexpression of MEP1A in PDAC was associated with invasion. Next, we investigated the combined effects of Lut, a DPYD suppressor, and 5‐FU on DPYD‐overexpressing xenograft tumors and PDAC of Pdx1‐Cre; LSL‐KrasG12D/+; Trp53flox/flox(KPPC) mice. Neither single administration of 5‐FU nor Lut showed significant inhibitory effects; however, the combined administration of 5‐FU and Lut exhibited a significant tumor‐suppressive effect in both the xenograft tumors and KPPC models. Conclusion We have elucidated that DPYD expression contributes to proliferation, invasiveness, and 5‐FU resistance, in PDACs. The combination therapy of Lut and 5‐FU holds the potential for enhanced efficacy against PDACs.